Clinical, Radiological and Pathological Characteristics Between Cerebral Small Vessel Disease and Multiple Sclerosis: A Review - Wang, Bijia; Li, Xuegang; Li, Haoyi; Xiao, Li; Zhou, Zhenhua; Chen, Kangning; Gui, Li; Hou, Xianhua; Fan, Rong; Chen, Kang; Wu, Wenjing; Li, Haitao; et al. (Frontiers in Neurology, 2022)
Cerebral small vessel disease (CSVD) and multiple sclerosis (MS) are a group of diseases associated with small vessel lesions, the former often resulting from the vascular lesion itself, while the latter originating from demyelinating which can damage the cerebral small veins. Clinically, CSVD and MS do not have specific signs and symptoms, and it is often difficult to distinguish between the two from the aspects of the pathology and imaging. Therefore, failure to correctly identify and diagnose the two diseases will delay early intervention, which in turn will affect the long-term functional activity for patients and even increase their burden of life. This review has summarized recent studies regarding their similarities and difference of the clinical manifestations, pathological features and imaging changes in CSVD and MS, which could provide a reliable basis for the diagnosis and differentiation of the two diseases in the future.